Emerging innovations in agile software development - Imran Ghani 1975-; Dayang Norhayati Abang Jawawi; Dorairaj, Siva 1972-; Sidky, Ahmed (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series, 2016)
This book focuses on the use of agile methodologies to manage, design, develop, test and maintain software projects, emphasizing research-based solutions for contemporary software development